2021
DOI: 10.3389/fimmu.2021.724411
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Relationship Between the Expression of B Cell Mature Antigen and the Classification, Stage, and Prognostic Factors of Multiple Myeloma

Abstract: The expression level of BCMA in bone marrow of 54 MM patients was detected in this study to explore the relationship between the BCMA expression and the classification, stage, and prognostic factors of MM. The BCMA expression level of the stable group and remission group was lower than that of the newly diagnosed group and relapse group (P=0.001). There was no significant difference in BCMA expression of MM patients in different types and stages (P>0.05), but it was found that for the newly diagnosed MM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 39 publications
(46 reference statements)
0
2
2
Order By: Relevance
“…In tumor research, a MM study has reported that there was no significant association between sBCMA levels and serum creatinine (SCr). 30 The present study also found poor correlation with renal parameters.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…In tumor research, a MM study has reported that there was no significant association between sBCMA levels and serum creatinine (SCr). 30 The present study also found poor correlation with renal parameters.…”
Section: Discussioncontrasting
confidence: 66%
“…In tumor research, a MM study has reported that there was no significant association between sBCMA levels and serum creatinine (SCr). 30 The present study also found poor correlation with renal parameters. Renal damage in SLE is not synchronized with immune disruption, and autoantibodies present preceding the initial clinical symptoms by several years.…”
Section: Discussioncontrasting
confidence: 66%
“…Studies have shown that the BCMA expression is constricted to the mature B-lymphoid compartment, making it a promising target in patients with MM [30]. Many studies have reported the expression of BCMA on MM cells, and selectively on plasma cells in normal tissues [23,31,32]. Clinical samples have also been analyzed to explore the range of BCMA expressions [33,34].…”
Section: Emergence Of B-cell Maturation Antigen (Bcma) As a Promising...mentioning
confidence: 99%
“…Regarding CRS management, most patients were diagnosed with grade-1 CRS, which was considered manageable [ 32 ]. Humanized BCMA and CD3 BiTes were developed, namely, PF-3135, and although no serious adverse event was reported, the clinical benefit rate was 41%, with 35% of patients displaying stable disease [ 34 , 35 ]. Additionally, BCMAxCD3 BiTes was also developed, called REGN5458; however, the results of the study reported that one out of three patients had stable disease [ 36 ].…”
Section: Anti-bcma Potential For Multiple Myelomamentioning
confidence: 99%
“…Although no direct comparison was made between the use of anti-BCMA and the usual regimen of multiple myeloma, the regimen using rituximab, lenalidomide, and bendamustine showed a complete response rate of 64%, which was higher compared with anti-BCMA [ 32 ]. However, the results of a case series also reflected the failure of CAR-T-cell therapy, which might be explained by the increase in anti-CAR-T-cell antibodies on the second infusion of the treatment [ 34 ]. The treatment can be used as maintenance therapy due to its minimal adverse effects.…”
Section: Anti-bcma Potential For Multiple Myelomamentioning
confidence: 99%